1999
DOI: 10.1021/es9804969
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Fluorescent Whitening Agents in the River Glatt

Abstract: With the use of computer simulation (AQUASIM), the dynamic behavior of the two fluorescent whitening agents (FWAs) that are currently used in laundry detergents in Switzerland (DSBP, a distyrylbiphenyl, and DAS 1, a diaminostilbene) has been evaluated quantitatively for the River Glatt, a small highly polluted stream in Switzerland. The one-dimensional simulation was based on independently determined photolysis and sorption rate constants, and measured FWA concentrations at the beginning of the studied river s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…It has been demonstrated that photoirradiation reduces the fluorescence intensity by decomposing fulvic and humic acids (Moran et al, 2000;Wu et al, 2005), tryptophan-like component (Moran et al, 2000;Mostofa et al, 2007b), and FWAs or household detergents (Poiger et al, 1999;Mostofa et al, 2005aMostofa et al, , 2010 in natural waters. On the other hand, microbial degradation has been observed to either enhance or decrease the fluorescence intensity in natural waters.…”
Section: (Continued)mentioning
confidence: 99%
“…It has been demonstrated that photoirradiation reduces the fluorescence intensity by decomposing fulvic and humic acids (Moran et al, 2000;Wu et al, 2005), tryptophan-like component (Moran et al, 2000;Mostofa et al, 2007b), and FWAs or household detergents (Poiger et al, 1999;Mostofa et al, 2005aMostofa et al, , 2010 in natural waters. On the other hand, microbial degradation has been observed to either enhance or decrease the fluorescence intensity in natural waters.…”
Section: (Continued)mentioning
confidence: 99%
“…A well studied example, where direct phototransformation in surface waters is a relevant environmental removal process, are fluorescent whitening agents, a class of high production volume chemicals widely used in laundry detergents and paper and cloth manufacturing [24][25][26][27]. A limited number of QSARs concerning very specific photoreactions, such as the photohydrolysis of aromatic halides [28], have been derived to date.…”
Section: Prediction Of Indirect Phototransformation In Surface Watersmentioning
confidence: 99%
“…Their widespread and massive usage and their persistent nature allow FWAs to be ubiquitously detected in wastewaters and in natural rivers, lakes, and oceans. For example, FWA concentrations are at a level of a few micrograms per liter (µg l −1 ) in sewage effl uent (Poiger et al 1998) and rivers Poiger et al 1999;Hayashi et al 2002;Hayakawa et al 2005) and at 0.1 µg l −1 in inland bays (Hayashi et al 2002) and lakes Yamaji et al, in preparation). Detergent surfactant, i.e., linear alkylbenzenesulfonate, is so biodegradable that it is not detected widely in natural waters as are FWAs.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of FWAs in Switzerland provided basic information on their distribution and behavior in rivers and lakes Poiger et al 1999). FWA concentrations in Swiss rivers were dependent on the discharge from sewage treatment plants that serviced a large population in the catchments, and from chemical plants manufacturing FWA in Switzerland for commercial export.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation